1997
DOI: 10.1159/000117405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Seropositivity and Drug Abuse on Cognitive Function

Abstract: Fifty-eight HIV-positive drug abusers and 22 HIV-positive nondrug abusers at stages II-III and IV of the Centers for Disease Control classification were evaluated neuropsychologically. The study confirmed previous findings that drug abuse has a negative influence on cognitive function. It also emerges that seropositivity affects cognitive function, although the poor performance of group II-III patients compared to group IV may be explained by factors related to seropositivity (anxiety and panic) rather than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…(13) The prevalence of neurologic complications of AIDS in patients admitted to hospital due to this disease was of the order of 40%, similar to reports in the literature from the mid 1980s onwards. (9,14,15) The percentage of AIDS patients seeking care due to a specific neurologic complaint in our study was 15.7%, while a further 5.1% sought care for a neurologic complaint plus other clinical symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…(13) The prevalence of neurologic complications of AIDS in patients admitted to hospital due to this disease was of the order of 40%, similar to reports in the literature from the mid 1980s onwards. (9,14,15) The percentage of AIDS patients seeking care due to a specific neurologic complaint in our study was 15.7%, while a further 5.1% sought care for a neurologic complaint plus other clinical symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, even if the results of Corsi Test and Block Design reached low significance, they showed a tendency towards an involvement of subcortical functions, that was more stressed by the result of Digit Symbol. These data, as stated by the results of Zung Scale, were not influenced by depression, a possible confounding factor that can be also excluded in the advanced stages of the disease, as already shown, and currently supported in a previous work [15]. Thus CD4 count is more closely associated with cognitive performance than disease stage.…”
Section: Discussionsupporting
confidence: 86%
“…It should be noted, however, studies that show increased cognitive impairment in HIV-infected drug abusers (e.g., Grassi et al, 1997) are in stark contrast to studies that show no difference in HAD incidence between drug abusers and non-abusers (e.g., Selnes et al, 1997). Jernigan et al (2005) recently demonstrated no differences in brain volume between HIV-infected/ METH abusers and non-infected/non-METH abusers using MRI scans of a multiple areas including the thalamus, basal ganglia structures including the nucleus accumbens and caudate nucleus, hippocampus, amygdala, and the four outer lobes of the cerebral cortex.…”
Section: Hiv + Cocaine And/or Methamphetamine Neurotoxicitymentioning
confidence: 99%